(untitled) (Journal of human and social sciences, 2023)
The search for financing sources for economic development and reconstruction in Libya is one of the main challenges facing post-2011 development plans, amid infrastructure damage, unstable public revenues, and the prioritization of salaries over development in the national budget. This study proposes Islamic sukuk as a tool for financing development and reconstruction in Libya, drawing on contemporary international experiences from Malaysia, Sudan, Saudi Arabia, and the UAE, using a comparative approach. The study presents a model of government participation sukuk called “Reconstruction Sukuk,” aimed at funding reconstruction and infrastructure projects, benefiting both economic development and sukuk holders. The study recommends establishing a legal framework for these sukuk, creating a supervisory authority to issue and monitor them, ensuring Sharia compliance, and raising public awareness about the importance of sukuk investment, free from usury concerns. Keywords: Islamic sukuk, economic development, reconstruction, Islamic finance, Libya.